Perancangan Tata Letak Fasilitas Lantai Produksi Modern Rice Mill Plant (MRMP) dengan Metode Systematic Layout Planning - Arifah Chandra Putri Gemilang; Aditya Maharani; Dian Asa Utari (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
Abstract - One of the manufacturing companies in Indonesia is developing a modern rice mill plant (MRMP) project in Jember. The infrastructure development of the project requires some planning, one of which is a good layout design. The layout design in the project has problems including the arrangement of machinery that is not in accordance with the production flow, the utilization of the available area is not maximized, and does not pay attention to the close relationship between facilities so that it will cause back tracking and excessive movement that will harm the company. Solving these problems can be done by designing a new facility layout using the Systematic Layout Planning (SLP) method. The results of the research using this method were obtained as many as 4 layout proposals, then one layout proposal was chosen, namely layout 4. The selected layout proposal has a difference in OMH value and total material handling mileage with the highest initial layout and can increase efficiency in material handling by 28.88 % on total material handling mileage and 37.47% efficiency on material handling costs per day.